Internationalization process of skypro shoes in the east coast of the US - Neves, Ana Luisa Furtado (2017)
This work project studies the internationalization potential of Abotoa SA, in particular to Skypro, its footwear brand targeted at aviation professionals, to the East Coast of the US. I firstly developed a company overview followed by a detailed analysis of country criteria based on population, country risk, the airline and footwear industries, consumer behavior and aviation professionals’ profile. Based on company information, statistic and governmental data, as well as professional insights from clients and aviation professionals, I further developed the internationalization plan, focusing on the B2C market, concluding that it will bring benefits to the company.